Legal regulations of service order in the USSR militia in the 20s of the 20th century - S. V. Vasyliev (Bulletin of Kharkiv National University of Internal Affairs)
The scientific paper is devoted to the problems of legal regulations of service in the USSR militia in the 20s of the 20th century. Legislative and by-laws adopted by the authorities of the Ukrainian SSR during the period under study were used. Some archival documents containing orders of the militia authorities regulating the service were introduced into scientific circulation.